Raising antiracist children : a practical parenting guide - Hawthorne, Britt; Yglesias, Natasha (Simon Element, 2022)
"Raising antiracist children is an essential goal for parents, caregivers, and educators, but it can be hard to know where to start. Let Britt Hawthorne--an acclaimed teacher and advocate--be your guide. Raising Antiracist Children is an interactive road map to incorporating the tools of inclusivity and activism into everyday life"--